Azetidinium lead iodide for perovskite solar cells. Issue 39 (22nd September 2017) - Pering, S. R.; Deng, W.; Troughton, J. R.; Kubiak, P. S.; Ghosh, D.; Niemann, R. G.; Brivio, F.; Jeffrey, F. E.; Walker, A. B.; Islam, M. S.; Watson, T. M.; Raithby, P. R.; et al.
Abstract : Azetidinium lead iodide has been prepared for the first time; it is a stable, bright orange material that can act as the absorber layer in solar cells. Abstract : Hybrid organic–inorganic perovskites have been established as good candidate materials for emerging photovoltaics, with device efficiencies of over 22% being reported. There are currently only two organic cations, methylammonium and formamidinium, which produce 3D perovskites with band gaps suitable for photovoltaic devices. Numerous computational studies have identified azetidinium as a potential third cation for synthesizing organic–inorganic perovskites, but to date no experimental reports of azetidinium containing perovskites have been published. Here we prepare azetidinium lead iodide for the first time. Azetidinium lead iodide is a stable, bright orange material which does not appear to form a 3D or a 2D perovskite. It was successfully used as the absorber layer in solar cells. We also show that it is possible to make mixed cation devices by adding the azetidinium cation to methylammonium lead iodide. Computational studies show that the substitution of up to 5% azetidinium into the methylammonium lead iodide is energetically favourable and that phase separation does not occur at these concentrations. Mixed azetidinium–methylammonium cells show improved performance and reduced hysteresis compared to methylammonium lead iodide cells.